Motivating English-Language Learners through Drama Techniques - Gill, Cham Kaur (INTI International University, 2007)
The focus of this paper is on the use of drama in English-Language learning. It discusses the writer’s use of drama techniques in teaching his language-learners at Bond University, Australia. The writer presents the advantages of drama over traditional teaching methodology and discusses the characteristics of learners and teachers involved in the application and such techniques. Throughout the paper, reference is made of the findings and philosophies of researchers and practitioners associated with the use of drama strategies. It concludes with the suggestion that the relevant authorities should recognize drama as an innovative strategy and consider raising its profile.